Handbook of trauma, traumatic loss, and adversity in children : development, adversity's impacts, and methods of intervention - Nader, Kathleen (New York, NY : Routledge, 2019)
The Handbook of Trauma, Traumatic Loss, and Adversity in Children is a developmentally oriented book rich with findings related to child development, the impact of trauma on development and functioning, and interventions directed at treating reactions to trauma. Aspects of attachment and parenting and the use of interrelationships toward therapeutic ends are included in each age-related section of the book, ranging from 0 to 18+. Consolidating research from a range of disciplines including neurobiology, psychopathology, and trauma studies, chapters offer guidance on the potentially cascading effects of trauma, and outline strategies for assisting parents and teachers as well as children. Readers will also find appendices with further resources for download on the book's website. Grounded in interdisciplinary research, the Handbook of Trauma, Traumatic Loss, and Adversity in Children is an important resource for mental health researchers and professionals working with children, adolescents, and families during the ongoing process of healing from traumatic exposure.
OCLC-licensed vendor bibliographic record.
Keywords: Post-traumatic stress disorder in children; Post-traumatic stress disorder in children -- Treatment; PSYCHOLOGY / Psychotherapy / Child & Adolescent; PSYCHOLOGY / Psychopathology / Post-Traumatic Stress Disorder (PTSD); PSYCHOLOGY / Mental Health